CLASS CULTURE AND THE ACADEMIC STRESS OF DIGITAL NATIVES GENERATIONS - Muchsini, Binti; Siswandari, Siswandari (LPMPP Universitas Negeri Yogyakarta, 2020)
The culture Digital Natives Generations (DNG) are important considerations for lecturers in designing their courses because they are a generation that is very familiar with the technology. The DNG will feel pressured if the learning process is similar to that of the previous generation. Therefore, the purpose of this study is to examine the effect of cultural values in the classroom that may lead to the academic stress of DNG. The research uses quantitative research methods. The instruments of cultural values in the classroom refer to Hofstede's cultural dimension, while Academic Stress (AS) refers to Gadzella’s Student-Life Stress Inventory, with 152 respondents representing students at Sebelas Maret University Indonesia. Data analysis was performed using simple regression analysis with the aid of MINITAB. The results show that there are significant influence of cultural values in the classroom Power Distance (PD), collectivism individualism (CI), feminism masculinity (FM), uncertainty avoidance (UAI), and long-term orientation (LTO) on AS (p < 0.05). The results of the study could be utilized to determine the cultural values in the classroom that could be incorporated into the design of learning models so as to minimize the AS of DNG at higher education.